2023
DOI: 10.1021/acsnano.3c04366
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials Solutions for Contraception: Concerns, Advances, and Prospects

Zhenning Su,
Tian Diao,
Helen McGuire
et al.

Abstract: Preventing unintentional pregnancy is one of the goals of a global public health policy to minimize effects on individuals, families, and society. Various contraceptive formulations with high effectiveness and acceptance, including intrauterine devices, hormonal patches for females, and condoms and vasectomy for males, have been developed and adopted over the last decades. However, distinct breakthroughs of contraceptive techniques have not yet been achieved, while the associated long-term adverse effects are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 181 publications
0
2
0
Order By: Relevance
“…The progressions in the field of nanotechnology have resulted in notable enhancements in contraceptive methodologies throughout the last several decades . The effectiveness of immuno-contraceptive vaccines using chitosan nanoparticles has been shown in the delivery of peptides and proteins, showcasing enhanced uptake by dendritic cells and extended presence in lymph nodes . Further investigation revealed that the use of disposable polymer-based polyethylene sebacate particles demonstrated efficacy in the administration of an HSA peptide-1 vaccination.…”
Section: Nanotech Advancements For Male and Female Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progressions in the field of nanotechnology have resulted in notable enhancements in contraceptive methodologies throughout the last several decades . The effectiveness of immuno-contraceptive vaccines using chitosan nanoparticles has been shown in the delivery of peptides and proteins, showcasing enhanced uptake by dendritic cells and extended presence in lymph nodes . Further investigation revealed that the use of disposable polymer-based polyethylene sebacate particles demonstrated efficacy in the administration of an HSA peptide-1 vaccination.…”
Section: Nanotech Advancements For Male and Female Contraceptionmentioning
confidence: 99%
“…242 The effectiveness of immuno-contraceptive vaccines using chitosan nanoparticles has been shown in the delivery of peptides and proteins, showcasing enhanced uptake by dendritic cells and extended presence in lymph nodes. 243 Further investigation revealed that the use of disposable polymer-based polyethylene sebacate particles demonstrated efficacy in the administration of an HSA peptide-1 vaccination. The use of chitosan-DNA nanoparticles has shown significant efficacy and safety in augmenting the immune response of a mCRISP1 DNA contraceptive vaccination.…”
Section: Nanotech Advancements For Male and Female Contraceptionmentioning
confidence: 99%
“…Since its initial report in 2022, the concept of cuproptosis has garnered considerable attention, finding applications in diverse fields such as cancer treatment, antibacterial therapies, and Alzheimer's disease research. [115][116][117][118] The study of copper, long regarded as a compelling subject, has unveiled promising anti-cancer potentials through investigations into cuproptosis inducers. The rapid evolution of nanotechnology in the medical domain has propelled the development of agents inducing cuproptosis.…”
Section: Summary: Challenges and Prospectsmentioning
confidence: 99%
“…As regards the mechanism of action, ferredoxin‐1 (FDX1) and lipoyl synthase (LIAS) regulate dihydrolipoamide S‐acetyltransferase (DLAT) to undergo lipoylation. [ 21–23 ] This results in the reduction of Cu 2+ and the oligomerization of lipoylated DLAT, leading to proteotoxic stress and eventually cell death. In addition, the endogenous overproduced glutathione (GSH) acts as a natural Cu chaperone in cells inhibiting cuproptosis by working as a thiol‐containing copper chelator.…”
Section: Introductionmentioning
confidence: 99%